The Disk Substructures at High Angular Resolution Project (DSHARP): IX. A high definition study of the HD 163296 planet forming disk - Isella, Andrea; Dullemond, Cornelis (Arxiv, 2018)
ALMA observations of protoplanetary disks acquired by the Disk Substructure at High Angular Resolution Project (DSHARP) resolve the dust and gas emission on angular scales as small as 3 astronomical units, offering an unprecedented detailed view of the environment where planets form. In this article, we present and discuss observations of the HD 163296 protoplanetary disk that imaged the 1.25 mm dust continuum and $^{12}$CO J=2-1 rotational line emission at a spatial resolution of 4 and 10 au, respectively. The continuum observations resolve and allow us to characterize the previously discovered dust rings at radii of 67 and 100 au. They also reveal new small scale structures, such as a dark gap at 10 au, a bright ring at 15 au, a dust crescent at a radius of 55 au, and several fainter azimuthal asymmetries. The observations of the CO and dust emission inform about the vertical structure of the disk and allow us to directly constrain the dust extinction optical depth at the dust rings. Furthermore, the observed asymmetries in the dust continuum emission corroborate to the hypothesis that the complex structure of the HD 163296 disk is the result of the gravitational interaction with yet unseen planets.
Gesehen am 18.08.2020